PENGARUH GAYA HIDUP, MOTIVASI, DAN PERSEPSI KONSUMEN PRIA DALAM PENGAMBILAN KEPUTUSAN PEMBELIAN PADA SALON TIARA DI KOTA MALANG - Meireni Grace Posmauli Napitupulu (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
This research aims to identify and analyze the effect of simultaneous and partial on decision making of customer in Tiara Salon Malang. To determine how much influence the independent variables (life style, motivation, and perception) on the dependent variable (decision making). Instruments used in the study was a questionnaire. This type of form of validity test, reliability test, and classical assumption. Hypothesis test using the F test and t test. To analyze the data used is linear regression and regression testing classical assumption of normality, multicollinearity test, and heteroscedasticity test. The results showed that simultaneous life style, motivation, and perception variables has a significant effect on decision making. Partially perception variable effect of significant influence, while the life style and motivation are not significant influence of decision making in Tiara Salon Malang.Keywords: life style, motivation, perception, and decision making